Precursor B Lymphoblastic Lymphoma Involving the Stomach - Masaya Iwamuro; Yoshinari Kawai; Yasuhide Yamawaki; Katsuyoshi Takata; Kazuhide Yamamoto (Case Reports in Gastrointestinal Medicine)
Precursor B lymphoblastic lymphoma is a high-grade neoplasm arising from precursor lymphocytes of B-cell lineage. Extranodal sites such as the skin and bone are often involved, but gastrointestinal lesions of this disease are rarely encountered. Due to the infrequency, macroscopic forms of the gastrointestinal lesions have not been fully described. In this report, we present a case of precursor B lymphoblastic lymphoma involving the stomach, pancreas, bone, and bone marrow. Esophagogastroduodenoscopy showed multiple flat elevated lesions with irregular mucosa in the stomach.